Occupational benefit perception of acute and critical care nurses: A qualitative meta-synthesis - Liu, Shuyang; Duan, Xia; Han, Peng; Shao, Haiyan; Jiang, Jinxia; Zeng, Li (Frontiers in Public Health, 2022)
Background: With the development of society, nurses have an increasingly more important role in the medical team. At the same time, due to various reasons, the number of active nurses is continuously decreasing, and the shortage of nursing personnel is becoming ever more serious. The COVID-19 pandemic made these clinical problems more serious. As the department with the greatest work pressure and the most intense pace, acute and critical care nurses are already facing serious problems related to job burnout and dismission. In the context of the COVID-19 pandemic, these problems should be solved urgently. Furthermore, with the rise of positive psychology, many scholars are turning their research direction to the positive professional experience of nurses so as to get inspiration to encourage nurses to face work with an optimistic attitude and guide nursing managers to better retain nursing talents. Objective: The purpose of this paper is to summarize and evaluate the positive emotional experience and professional benefit of acute and critical care specialist nurses in the process of work. So as to better interpret their occupational benefit perception and guide nursing managers in adopting positive measures and promoting the development of high-quality nursing. Methods: Cinahl plus and other twelve databases were searched for relevant literature. Meta-aggregation was used to synthesize the findings of the included studies. Results: From a total of 12 articles included in this study, 55 main results were presented, 8 new categories were integrated, and three themes were formed: professional identity, social support, and personal growth. The professional identity included: being proud of professional ability and increasing professional value; social support included: friends and family support, organizational, environmental support, peer support, and support of patients and their families; personal growth included realizing self-worth and promoting self-development. Conclusion: Hospital managers should pay attention to the positive emotional experience of nurses in work and based on this, provide practical and beneficial protection for nurses from the aspects of salary, learning opportunities, working environment, social support and internal personality, stimulate work enthusiasm, guide nurses to correctly face negative emotions and occupational pressure, and improve the sense of professional benefit.